Differential role of CD97 in interleukin-8-induced and granulocyte-colony stimulating factor-induced hematopoietic stem and progenitor cell mobilization - Melissa van Pel; Henny Hagoort; Mark J. Kwakkenbos; Jörg Hamann; Willem E. Fibbe (Haematologica, 2008)
CD97 is broadly expressed on hematopoietic cells and is involved in neutrophil migration. Since neutrophils are key regulators in HSC/HPC mobilization, we studied a possible role for CD97 in interleukin-8 and granulocyte-colony stimulating factor-induced HSC/HPC mobilization. Mobilization was absent in mice receiving CD97 mAb followed by interleukin-8, while granulocyte-colony stimulating factor-induced mobilization remained unaltered following anti-CD97 administration. Furthermore, combined administration of CD97 mAb and IL-8 induced a significant reduction in the neutrophilic compartment. We hypothesize that the absence of interleukin-8-induced HSC/HPC mobilization after CD97 mAb administration is due to its effect on neutrophil function.